1999
DOI: 10.1007/s002210050735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the neuronal plasticity along the neuraxis of the vibrissal sensory system of adult rat following unilateral infraorbital nerve damage and subsequent regeneration

Abstract: The aim of the present study was to examine the physiological consequences of a unilateral infraorbital nerve lesion and its regeneration at different levels of the somatosensory neuraxis. In animals whose right infraorbital nerve had been crushed, a large unresponsive area was found in the main brainstem trigeminal nucleus (Pr5). Responses evoked by ipsilateral vibrissal deflection in the middle of Pr5 reappeared only on days 22-35 after the nerve had been transected, whereas recovery from the nerve crush too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…A likely explanation is that a regenerating axon follows a channel, possibly established by Schwann cells distal to the transection (Fawcett and Keynes 1990), which leads to a single whisker follicle. The misrouting of regenerating distal axons will have a substantially deleterious effect on CNS processing that depends on high-resolution spatial mapping (Kis et al 1999;Waite and Cragg 1982).…”
Section: Discussionmentioning
confidence: 99%
“…A likely explanation is that a regenerating axon follows a channel, possibly established by Schwann cells distal to the transection (Fawcett and Keynes 1990), which leads to a single whisker follicle. The misrouting of regenerating distal axons will have a substantially deleterious effect on CNS processing that depends on high-resolution spatial mapping (Kis et al 1999;Waite and Cragg 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than subsiding, however, the interest in furthering the anatomical knowledge of these nuclei expanded considerably more recently, with the trigeminal system becoming a model to study development and neural pattern formation Waite and De Permentier, 1997), sensory information processing (Szwed et al, 2003;Jones et al, 2004), sensorimotor integration (Tsuboi et al, 2003), and neural plasticity (Melzer and Smith, 1998;Kis et al, 1999;Machín et al, 2004), to develop models of pain (Vos et al, 2000), or to design artificial sensors in robotics (Fend et al, 2003).…”
mentioning
confidence: 99%
“…In general, it has been shown that nerve crush injuries result in fewer reinnervation errors than repaired nerve cut injuries and are associated with good recovery (Wall et al 1983). The index of topography and the cutaneous threshold measures used in this study were employed to establish a more precise, quantitative measure of physiological recovery from nerve crush injuries (Kawakami et al 1989;Kis et al 1999;Korodi and Toldi 1998). These quantitative measures allow for statistical comparisons between various nerve repair techniques (e.g., end-to-end repair versus tubulization) (see Lundborg et al 1997;Meyer et al 1997) and possible rehabilitative therapies (e.g., Florence et al 2001;Xerri et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that minor regeneration errors do occur following nerve crush injuries (Munger and Renehan 1989;Povlsen et al1994;Sanders and Zimmerman 1986) and that these errors can distort cortical topography (Kawakami et al 1989;Kis et al 1999;and Korodi and Toldi 1998). The implication of these earlier studies is that cutaneous sensitivity in the reinnervated skin territories may be compromised by nerve crush injury.…”
Section: Introductionmentioning
confidence: 99%